KELIMPAHAN DAN KERAGAMAN JENIS IKAN FAMILI CHAETODONTIDAE BERDASARKAN KONDISI TUTUPAN KARANG HIDUP DI KEPULAUAN SPERMONDE SULAWESI SELATAN - Nurjirana, Nurjirana; Burhanuddin, Andi Iqbal (Hasanuddin University, 2017)
The family Chaetodontidae known as butterfly fishes (kepe-kepe) is a species that associated with coral by consumes coral polyp as its feed. This study aimed to determine the abundance and fish diversity of Chaetodontidae and to look the relationship of fish Chaetodontidae abundance with live coral coverage at Spermonde Island. To determines the abundance and fish diversity of Chaetodontidae by using direct census, while to determine the condition of coral reel used line intercept transect (LIT) method. This study was conducted for 6 (six) station at Spermonde Island by collecting data on depth 4 – 6 m with 3 replicate in each station. Result of study found 5 genera and consist of 16 species fishes from family Chaetodontidae. The overall of Chaetodontidae found is 70 Ind/250 m2 with the largest abundance in Kapoposang island (46 Ind/250 m2) and the smallest is Karanrang island (1 Ind/250 m2). Percentage of live coral coverage on research station at Spermonde Island at “good” to “bad” categories highest coral coverage at Badi island (72.6%) and the lowest is Balanglompo island (5%). Fish diversity of Chaetodontidae is high at station that dominated by Acropora coral. Abundance and fish diversity of Chaetodontidae are no relationship significantly on the percentage of live coral coverage of research station at Spermonde Island.Keyword : Chaetodontidae, coral reef, Spermonde.